Penghentian Proses Hukum Dalam Penanganan Perkara Dekriminalisasi - ALFONS ZAKARIA (Fakultas Hukum Universitas Mulawarman, 2008)
The implementation of law in society need values which always be obeyed, such as rule of lawand justice. However, sometime they cannot be applied simultaneously. The rule of law can be ignored inorder to achieve the justice. It can be seen on article 1 verse 2 of Indonesia Criminal Code which disregardprinciple of legality to give the justice for the offender. In practice, the example case is decriminalization. Ifan unlawful act is classified as decriminalization, as result all the current cases must be terminated. Thisarticle will explain about discontinuing the decriminalization case and the law on each phase of legalprocess are taken.Key words : dekriminalisasi (decriminalization), keadilan ( justice), proses hukum (legal process).